Static and dynamic crushing of polymeric lattices fabricated by fused deposition modelling and selective laser sintering – an experimental investigation. (February 2022) - Sun, Z.P.; Guo, Y.B.; Shim, V.P.W.
Highlights: Hybrid Structure, as geometrical hybrid of octet and rhombic dodecahedron, formulated to achieve the combination of their corresponding advantages. Dynamic compressive responses of three polymeric lattices examined experimentally, as lattices for energy absorption expected to shield an object from impact in practical applications. Selective laser sintered lattices collapse catastrophically under impact, although attaining favourable quasi-static performances. Fused deposition modelled lattices exhibit good energy absorption characteristics under both quasi-static and dynamic compression. Rate dependence observed in FDM lattices, accompanied with severer deformation localisation and strut failure. Abstract: Lightweight polymeric lattices, which display good energy absorption characteristics during crushing, are increasingly employed in impact protection applications. Lattices based on an octet, rhombic dodecahedron (RD) and a novel hybrid structure (HS), were fabricated by Selective Laser Sintering (SLS), and their dynamic responses were investigated via a drop-weight tester. Their stress-strain responses and crushing patterns were compared with quasi-static responses obtained using a universal testing machine. The experimental results show that SLS-fabricated lattices display good energy absorption performance under quasi-static compression, but collapse catastrophically when subjected to impact. To investigate the cause for the distinct responses under different deformation speeds, the quasi-static and dynamic tensile properties of the cell strut material were also examined. SLS-fabricated specimens are notably more brittle than those fabricated by another commonly used technique – Fused Deposition Modelling (FDM). Consequently, lattices fabricated by FDM were also tested. Unlike their SLS counterparts, FDM-fabricated lattices exhibit good energy absorption characteristics under both quasi-static and dynamic compression, as well as typical rate dependence, whereby the stress level increases with deformation speed. Compared with the traditional octet and RD, the novel HS lattice design shows superior energy absorption characteristics for all tests.